Subsequent Antituberculous Treatment May Not Be Mandatory Among Surgically Resected Culture-Negative Pulmonary Granulomas: A Retrospective Nationwide Multicenter Cohort Study. (9th November 2021) - Chung, Che-Liang; Huang, Wei-Chang; Huang, Hung-Ling; Chin, Chun-Shih; Cheng, Meng-Hsuan; Lee, Meng-Rui; Lin, Sheng-Hao; Wang, Jann-Yuan; Lin, Ching-Hsiung; Chong, Inn-Wen; Shih, Jin-Yuan; Yu, Chong-Jen
Abstract: Background: Histologic diagnosis of granuloma is often considered clinically equivalent to a definite diagnosis of pulmonary tuberculosis (TB) in endemic areas. Optimal management of surgically resected granulomatous inflammation in lung with negative mycobacterial culture results, however, remains unclear. Methods: From 7 medical institutions in northern, middle, and southern Taiwan between January 2010 and December 2018, patients whose surgically resected pulmonary nodule(s) had histological features suggestive of TB but negative microbiological study results and who received no subsequent anti-TB treatment were identified retrospectively. All patients were followed up for 2 years until death or active TB disease was diagnosed. Results: A total of 116 patients were enrolled during the study period. Among them, 61 patients (52.6%) were clinically asymptomatic, and 36 (31.0%) patients were immunocompromised. Solitary pulmonary nodule accounted for 44 (39.6%) of all cases. The lung nodules were removed by wedge resection in 95 (81.9%), lobectomy in 17 (14.7%), and segmentectomy in 4 (3.4%) patients. The most common histological feature was granulomatous inflammation (n=116 [100%]), followed by caseous necrosis (n=39 [33.6%]). During follow-up (218.4 patient-years), none of the patients developed active TB. Conclusions: In patients with surgically resected culture-negative pulmonary granulomas, the incidence rate of subsequent active TB is low. Watchful monitoring along with regular clinical, radiological, and microbiological follow-up, instead of routine anti-TB treatment, may also be a reasonable option. Abstract : The incidence of active tuberculosis in patients with surgically resected culture-negative pulmonary granulomas was very low. Regular clinical, radiological, and microbiological follow-up, instead of routine immediate antituberculosis treatment, may be a reasonable option.